Growth hormone increases dendritic spine density in primary hippocampal cell cultures. (February 2020) - Nylander, Erik; Zelleroth, Sofia; Stam, Frida; Nyberg, Fred; Grönbladh, Alfhild; Hallberg, Mathias
Abstract: Objective: Growth hormone (GH) is widely known for its peripheral effects during growth and development. However, numerous reports also suggest that GH exert pro-cognitive, restorative, and protective properties in the brain. In in vitro studies, the detection of dendritic spines, small protrusions extending from axons, can act as a marker for cognition-related function as spine formation is considered to be associated with learning and memory. Here we show that an acute 24-hour treatment of GH can increase dendritic spine density in primary hippocampal cell cultures. Design: Primary hippocampal cells were harvested from embryonic Wistar rats and cultured for 14 days. Cells were treated with supra-physiological doses of GH (10-1000 nM) and subjected to a high-throughput screening protocol. Images were acquired and analyzed using automated image analysis and the number of spines, spines per neurite length, neurite length, and mean area of spines, was reported. Results: GH treatment (1000 nM) increased the number of dendritic spines by 83% and spines per neurite length by 82% when compared to control. For comparison BDNF, a known inducer of spine densities, produced statistically non-significant increase in this setting. Conclusion: The results was found significant using the highest supra-physiological dose of GH, and the present study further confirms a potential role of the hormone in the treatment of cognitive dysfunction. Graphical abstract: Unlabelled Image Highlights: This study was designed using a novel high-throughput screening technique. GH increases dendritic spine density in primary hippocampal cell cultures. The results further confirm the role of GH as a cognitive enhancer.